Examining entrepreneurial intentions through the lens of university students’ attitudes - Ognjenović, Kosovka (Anali Ekonomskog fakulteta u Subotici, 2024)
The labour markets of the transition countries of Central and Eastern Europe relied on stronger growth of the corporate sector as a mechanism for integrating the growing number of laid-off workers. The Serbian labour market has had a similar experience. Decades after the start of economic reforms, however, the role of entrepreneurship as an integrative employment mechanism has not increased in importance, which is best evidenced by statistical data. This paper focuses on students’ intention to start their own business after graduation, and specifically examines the relationship between intention and personal attitudes. The experiment was conducted with two groups of students. The results indicate differences in students’ attitudes towards entrepreneurship that deepen according to faculty group, gender and year of study. From the students’ responses, it can be concluded that electrical engineering students, female economics students and students in higher years of study are more inclined towards entrepreneurship. This may have implications for measures to support the development of youth entrepreneurship.